2017
DOI: 10.1080/15332640.2017.1404953
|View full text |Cite
|
Sign up to set email alerts
|

Impairment of functioning and substance use in a Latino population

Abstract: This study investigated the association of academic outcomes, romantic relationships, and substance use (tobacco, marijuana, cocaine) with alcohol dependence in a sample of Latino (N = 1,143) college students. Secondary data analysis was conducted on measures of grade point average in college, relationship satisfaction, drug use, and alcohol dependence. Latino college students who reported alcohol dependency had significant relational dissatisfaction and poor academic outcomes. Thus, lower grade point average … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 32 publications
0
2
0
Order By: Relevance
“…Research shows the rates of substance use among Latino college students are high, surpassing the rates of substance use of any other Latino age group (G. X. Ma & Shive, 2000; McCabe et al, 2007; Mercado et al, 2019; Substance Abuse and Mental Health Services Administration, 2019; Zamboanga, 2005). This pattern of substance use has been found to affect Latino college students in other life domains.…”
Section: Acculturative Stress and Alcohol Use Among Latino College St...mentioning
confidence: 99%
See 1 more Smart Citation
“…Research shows the rates of substance use among Latino college students are high, surpassing the rates of substance use of any other Latino age group (G. X. Ma & Shive, 2000; McCabe et al, 2007; Mercado et al, 2019; Substance Abuse and Mental Health Services Administration, 2019; Zamboanga, 2005). This pattern of substance use has been found to affect Latino college students in other life domains.…”
Section: Acculturative Stress and Alcohol Use Among Latino College St...mentioning
confidence: 99%
“…This pattern of substance use has been found to affect Latino college students in other life domains. For example, in a sample of Mexican American college students, Mercado et al (2019) found that alcohol dependency was associated with lower romantic relationship satisfaction and a lower grade point average.…”
mentioning
confidence: 99%